Chapter 7 Critical race theory matters in sport - Hylton, Kevin (Taylor & Francis, 2021)
"In the decade since Kevin Hylton’s seminal book ‘Race’ and Sport: Critical Race Theory was published, racialised issues have remained at the forefront of sport and leisure studies. In this important new book, Hylton draws on original research in contemporary contexts, from sport coaching to cyberspace, to show once again that Critical Race Theory is an insightful and productive tool for interrogating problematic social phenomena.